La motricidad gruesa y su incidencia en el desarrollo del área cognitiva de los niños y niñas del primer año de educación general básica de la escuela Ciudad de Pasaje y la unidad educativa Manuela Cañizares del cantón pasaje en el período lectivo 2013-2014. - Campoverde Vega, Diana Piedad (2014)
This research is of vital educational and critical in the deployment of the gross motor skills of children, since the natural energy that have forced to be in constant motion, so it is necessary to use that motor action and manage it positively in performing motor exercises, as well as the mental and conscious representation thereof.